Work-related musculoskeletal disorder and its associated factors among bank workers in Ethiopia: A systematic review and meta-analysis - Abebe Kassa Geto; Hussien Mekonnen; Tesfalem Tilahun Yemane; Endalew Minwuye Andargie; Birhanu Sewunet; Tarikuwa Natnael; Chala Daba (PLoS ONE, 2025)
Introduction Work-related musculoskeletal disorders are among the major global public health problems and contributors to disability and workers’ absence in occupational areas which certainly disrupts work productivity and expected results. In Ethiopia, different studies investigated work-related musculoskeletal disorders. However, the findings were not consistent and conclusive enough, and there is no nationwide data representing this growing public health concern. This in turn hinders the efforts of intervention activities. Therefore, this study aimed to estimate the pooled prevalence of and factors associated with work-related musculoskeletal disorder among bank workers in Ethiopia. Methods To retrieve all the relevant studies, international databases such as PubMed/MEDLINE, CINAHL, LIVIVO, African Journals Online, African Index Medicus (AIM), HINARI, Science Direct, Cochrane Library, Google Scholar, Semantic Scholar, and Google were used. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline was followed for this study. The extracted data were analyzed using STATA 17 software. The heterogeneity of the included studies was determined by the Higgs I2 statistics. With a 95% confidence interval, this meta-analysis with the random-effects model was carried out to determine the pooled prevalence of work-related musculoskeletal disorder. Result In this meta-analysis, eight articles in total with 3399 study participants were included. The overall pooled prevalence of work-related musculoskeletal disorder was 57.41% (95%; CI: 38.87%, 75.95%; I2 = 99.4%; P = 0.000). Gender, job stress, physical activity, and work experience were found to be factors significantly associated with work-related musculoskeletal disorder. Conclusion A high prevalence of work-related musculoskeletal disorder among bank workers in Ethiopia was recorded. This underscores the importance of implementing effective intervention measures such as job rotation, job enrichment, extended breaks, mitigating negative social factors, and establishing physical exercise facilities to address the underlying issues.